“optimizacion del proceso de revestimiento con concreto mediante el uso del sistema slick line para el transporte de concreto en la construcción del pique principal marsa” - Fernández García, Robert Enmanuel (2016)
This research study seeks to optimize the lining process of the Master Shaft MARSA. Because due to the great distance that has to travel the concrete due to the deepening and geomechanical problems demand cubic meters of concrete grew exponentially deficient by the current system of transport, thus causing the search for new alternatives, opting for Slick Line system. The development of this research considers, first, determining the reality of the transport of concrete at the bottom of the shaft, which is done by using the bucket of services but this can only load one cubic meter per ride, making the coating process more slowly shaft, directly affecting other operations such as the assembly of metal, drilling and blasting set, placing compromised the deadline for completion of the project of building the Master Shaft MARSA. Then the described process lining shaft. In this step, the calculation of performance (linear meters of lining shaft) and cost ($ / ML) before and after executing the project is done. An economic evaluation of the project Slick Line is also presented through tables and graphs for better analysis. With the implementation of Transport concrete project with the Slick Line system managed to increase the performance (m3 / hr) transport concrete, thus translating into compliance with projected linear meters of lining shaft despite the increased cubic meters concrete.